Implementation of Knock Down Construction Planning in Brick Processing Bantilang (Tamalayang sub-district, Bontonompo sub-district, Gowa regency) - ., Imriyanti; ., Nasruddin; M, Pratiwi; ., Hartawan; A, Andi L S; S, Nurul; P, Difat S; I, Rada (Faculty of Engineering UNHAS, 2023)
Bantilang is a container that functions as a place for processing activities in producing bricks. The current form of Bantilang in Tamllayang Subdistrict is very simple, made at will, so that Bantilang cannot accommodate all processing activities. Bantilang's condition also did not last long, often experiencing damage due to strong winds and heavy rain. With the problems experienced by brick processors, a new Bantilang plan is needed to accommodate their needs in their activities as brick processors. The Knock Down form of Bantilang planning aims to provide a sense of security, comfort and increase brick production so that there will be an economic increase for the village community in Tamallayang sub-district. The Knock Down form is a form of disassembly that is applied to Bantilang planning. This is done to make brick processing land/yard more efficient and effective because processing activities are only carried out during the dry season. The number of brick processors in this sub-district is 88 families representing 1 person. The improvements achieved from this service activity are that 52% of brick processing activities can be accommodated, 43% of the Knock Down form is more effective, 58% of materials can be maintained, 60.23% of materials are not easily damaged by weather, 55.68% are practical for the land and 62 .50% provides a sense of security and comfort